The Influence of Diversity in Medium Activity Units in Increasing Economic Growth - Asni Asni; Masyadi Masyadi; Puji Rahmah (GENTARA: management and accounting research, 2026)
This research aims to analyze the influence of diversity in MSMEs on increasing economic growth. MSMEs are business units/organizations that are at a medium level of activity, not as small as micro businesses, but which also do not yet have a large scale which is generally the link between local job creation and wider economic integration. Diversity can include the diversity of human resources, the variety of backgrounds of business actors/workers, as well as the variety of networks and skills possessed by these units. Using a quantitative approach based on secondary data (regional economic indicators and economic unit characteristics), this research examines the relationship between diversity and economic growth indicators through a conceptual framework that emphasizes productivity, innovation, market expansion and resource allocation efficiency. The research results are expected to show that the higher the quality of diversity managed inclusively, the greater the contribution to economic growth through increasing productivity and the adaptive capacity of economic units to market changes. It is hoped that these findings will provide policy implications for the government and stakeholders to encourage the strengthening of an inclusive MSME/medium industry ecosystem, including training policies, fair access to financing, and strengthening collaborative networks across groups